Germany's fragile leadership role in European air defence: The need for adjustments at all levels of the European Sky Shield Initiative - Sven Arnold; Torben Arnold (Stiftung Wissenschaft und Politik (SWP), 2023)
With the European Sky Shield Initiative (ESSI), Germany has made its claim as the leader in European air defence. Taking a joint approach to defence is a good step forward, but difficult to implement. Important European partners, above all France and Italy, are currently unwilling to follow Germany's lead. The lack of political unity shows that Germany's proposal does not take European security interests sufficiently into account, has failed to convince partners, and leaves many questions unanswered on the strategic, military, industrial, and economic levels. If the ESSI is to noticeably improve Europe's air defence protection, Berlin must provide answers about strategic balance, the development of the European defence industry, and militarily effective solutions. The acquisition of individual military capabilities will not produce a European Sky Shield.
Keywords: 320; European air defence; European Sky Shield Initiative (ESSI); European security; Germany as a leader in air defence